A method for reducing the number of reliability formulae in reliability expression of weighted-k-out-of-n system - Higashiyama, Yoichi; Rumchev, Ventseslav (RAMS Consultants, 2008)
A weighted version of the k-out–of–n system is considered. In the disjoint products version of reliability analysis of weighted–k-out–of– n systems, it is necessary to determine the order in which the weight of components is to be considered. The k–out–of–n :G(F) system consists of n components; each component has its own probability and positive integer weight such that the system is operational (failed) if and only if the total weight of some operational (failure) components is at least k. This paper designs a method to compute the reliability in computing time and in memory space. The proposed method expresses the system reliability in fewer reliability formulae than those already published.